501 Hebrew verbs : fully conjugated in all tenses in an easy-to-learn format and alphabetically arranged - Bolozky, Shmuel, 1943- (Barron's foreign language guides., 2018)
Learning Hebrew becomes easier with this helpful guide to verbs and their roots! The most commonly used Hebrew verbs are arranged alphabetically in a table format, with English translation, and presented in all forms. Includes example sentences, common idioms, Hebrew roots, and English-Hebrew index, and more.